Electronic Learning System in Teaching Mathematics Enhancing Achievement among Students - Tamayo-Urbina, Charlotte S.; Dalayap, Reynaldo H. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigates the effectiveness of Computer-Aided Instruction (CAI) in improving mathematics achievement among 70 Grade 7 students over an eight-week period at Bacongco National High School. Using a quasi-experimental design, it compares CAI with traditional lecture-based teaching through pretest and posttest assessments. Grounded in Constructivist, Behaviorist, and Cognitive Load theories, the research explores how CAI may enhance active learning, reduce cognitive overload, and increase engagement. Participants were split into two groups: one received CAI-based instruction, while the other followed traditional methods. Pretest results showed both groups performed at a “weak” level with nearly identical scores (CAI: 14.34%, traditional: 14.29%), indicating similar academic baselines. After the intervention, both improved to a “developing” level (CAI: 20.06%, traditional: 20.86%). However, statistical analysis found no significant difference in posttest scores or mean gain scores (CAI: 5.71%, traditional: 6.57%, p > 0.05). While both approaches were equally effective in enhancing performance, the short duration of the study (eight weeks) may have limited CAI’s impact. The findings suggest CAI should be seen as a complementary tool rather than a replacement for traditional instruction. The study recommends longer-term implementation, development of localized CAI materials, and teacher training to maximize benefits. It contributes to the broader discourse on educational technology by affirming the comparable effectiveness of CAI and traditional methods, while emphasizing the need for strategic planning, contextual adaptation, and institutional support to optimize technology integration in education.